Getting teams to talk: development and pilot implementation of a checklist to promote interprofessional communication in the OR. Issue 5 (29th September 2005) - Lingard, L; Espin, S; Rubin, B; Whyte, S; Colmenares, M; Baker, G R; Doran, D; Grober, E; Orser, B; Bohnen, J; Reznick, R
Abstract : Background: Pilot studies of complex interventions such as a team checklist are an essential precursor to evaluating how these interventions affect quality and safety of care. We conducted a pilot implementation of a preoperative team communication checklist. The objectives of the study were to assess the feasibility of the checklist (that is, team members' willingness and ability to incorporate it into their work processes); to describe how the checklist tool was used by operating room (OR) teams; and to describe perceived functions of the checklist discussions. Methods: A checklist prototype was developed and OR team members were asked to implement it before 18 surgical procedures. A research assistant was present to prompt the participants, if necessary, to initiate each checklist discussion. Trained observers recorded ethnographic field notes and 11 brief feedback interviews were conducted. Observation and interview data were analyzed for trends. Results: The checklist was implemented by the OR team in all 18 study cases. The rate of team participation was 100% (33 vascular surgery team members). The checklist discussions lasted 1–6 minutes (mean 3.5) and most commonly took place in the OR before the patient's arrival. Perceived functions of the checklist discussions included provision of detailed case related information, confirmation of details, articulation of concerns or ambiguities, team building, education, and decision making. Participants consistently valued the checklist discussions. The most significant barrier to undertaking the team checklist was variability in team members' preoperative workflow patterns, which sometimes presented a challenge to bringing the entire team together. Conclusions: The preoperative team checklist shows promise as a feasible and efficient tool that promotes information exchange and team cohesion. Further research is needed to determine the sustainability and generalizability of the checklist intervention, to fully integrate the checklist routine into workflow patterns, and to measure its impact on patient safety.